Metaphase chromosome analysis by ligation-mediated PCR: heritable chromatin structure and a comparison of active and inactive X chromosomes. - Hershkovitz, M (1995)
We report that ligation-mediated PCR (LMPCR) can be used for high-resolution study of metaphase chromosomes, and we discuss the role of metaphase chromatin structure in the preservation of differentiated cell states. The X chromosome-linked human PGK1 (phosphoglycerate kinase 1) promoter region was investigated, and euchromatic active X chromosome (Xa) metaphase chromatin was compared with interphase Xa chromatin and to heterochromatic inactive X chromosome (Xi) metaphase and interphase chromatin. We find that (i) good-quality data at single-nucleotide resolution can be obtained by LMPCR analysis of dimethyl sulfate-treated intact metaphase cells; (ii) transcription factors present on the Xa promoter of interphase chromatin are not present on metaphase chromatin, establishing that the transcription complex on the PGK1 promoter must form de novo each cell generation; and (iii) the dimethyl sulfate reactivity pattern of Xa and Xi chromatin at metaphase is very similar to that of naked DNA. These results are discussed in the context of models for heritable chromatin structure and epigenetic mechanisms for cell memory, and they are also relevant to more general aspects of chromatin structure and differences between euchromatin and heterochromatin.